2016
DOI: 10.1080/13825585.2016.1269146
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in perceptions of memory strategy effectiveness for recent and remote memory

Abstract: We examined whether young and older adults hold different beliefs about the effectiveness of memory strategies for specific types of memory tasks and whether memory strategies are perceived to be differentially effective for young, middle-aged, and older targets. Participants rated the effectiveness of five memory strategies for 10 memory tasks at three target ages (20, 50, and 80 years old). Older adults did not strongly differentiate strategy effectiveness, viewing most strategies as similarly effective acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…While the present results are consistent with the view that older adults also choose to use external reminders as a means of avoiding cognitive effort, this tendency might be reduced if the act of setting reminders is itself seen as effortful. This possibility is congruent with previous research (Hertzog et al, 2012;Lineweaver et al, 2018) showing that older people choose strategies according to both their perceived difficulty and effectiveness, while younger people tend to consider effectiveness predominantly. Similarly, Hertzog et al (2017) suggested that older people tended to use rote repetition rather than switching to more effective strategies due to the cognitive effort involved in switching strategies.…”
Section: Discussionsupporting
confidence: 90%
“…While the present results are consistent with the view that older adults also choose to use external reminders as a means of avoiding cognitive effort, this tendency might be reduced if the act of setting reminders is itself seen as effortful. This possibility is congruent with previous research (Hertzog et al, 2012;Lineweaver et al, 2018) showing that older people choose strategies according to both their perceived difficulty and effectiveness, while younger people tend to consider effectiveness predominantly. Similarly, Hertzog et al (2017) suggested that older people tended to use rote repetition rather than switching to more effective strategies due to the cognitive effort involved in switching strategies.…”
Section: Discussionsupporting
confidence: 90%
“…This study also assumes that the educational strategies in memorizing the Quran could positively impact the performance of the memory as evident in the study by Frankenmolen et al (2018), which shows significant improvement on the memory performance of the intervention group based on the primary outcome measure on the memory functioning in daily life. This is also corroborated with the study by Lineweaver et al (2018) that memory strategies had hugely affected the functions of daily memory based on the opinion of the adult respondents. Based on the past studies on classification memory strategies, this study solely focuses on the internal memory strategies which consist of attention, rehearsal, repetition and chunking as well as the external memory strategies which refer to memory aids, exercise, sufficient sleep and balanced diet as healthy lifestyle is crucial for a good mental state and memory (The State of Queensland, 2017).…”
Section: Focus Of the Reviewsupporting
confidence: 88%
“…Therefore, appropriate educational strategies were executed in order to maximize the function of the memory based on the study by May and Einstein (2013), the memory strategies involved for the sensory memory are attention and automaticity, maintenance rehearsal, as well as elaborative rehearsal and chunking for the working memory as to ensure that the information could be activated. However, this review only focuses on the memory strategies of classification, internal and external based on the studies by Lineweaver et al (2018); Frankenmolen et al (2018).…”
Section: Focus Of the Reviewmentioning
confidence: 99%